Current view and prospect: Implantable pressure sensors for health and surgical care. Issue 3 (9th April 2020) - Honjol, Yazan; Rajkumar, Vijidha Shree; Parent‐Harvey, Caroline; Selvasandran, Kaviyanka; Kordlouie, Sarah; Comeau‐Gauthier, Marianne; Harvey, Edward; Merle, Geraldine
Abstract: Health monitoring and screening have entered a period of rapid change. Popular terminology refers to this as mobile health (mHealth), which is a direct evolution of eHealth, but is really data‐driven technology—sensors oriented for health care. Medical decision support through this technology is the first step towards more personalized and preventative medicine. Pressure is one of the easiest and most interesting physiological parameters to assess whether organs or biological systems are healthy in the body. Pressure recordings are commonly used for clinical diagnosis and monitoring; however, the invasiveness of current technologies and associated risks of infection limit the windows in which data can be gathered. This review discusses the importance of pressure in the body and how monitoring is performed. It also describes newer and commercially available sensors, as well as how they can be improved to become minimally invasive, fully wireless pressure sensors for continuous monitoring.